Computational first-principles and experimental characterization of Nb-X-Ti-based (X=Zr, Mo) and Fe-Cr-Ni-based high-entropy alloys - Mazo, João Henrique (2024)
Two Nb-X-Ti-based (X=Zr, Mo) refractory high-entropy alloys (RHEAs) and a Fe-Cr-Ni-based high-entropy stainless steel (HESS) were computationally modeled and characterized using density functional theory first-principles calculations, focusing on the characterization of their elastic properties. Novel experimental data were acquired and, combined with previously reported experiments, were utilized to further discuss and assess the quality of the developed and applied theoretical methodology. For each alloy, ten thousand supercells were generated using an in-house Python implementation of the maximum entropy principle. Only the ten highest free volume supercells were sampled for data production, and their results were averaged. The RHEAs were the first alloys to be simulated and were utilized to validate the theoretical methodology, which was then extended to the HESS. For the RHEAs, the structural values of both alloys matched experimental results, and simulations were used to identify the correct B2 structure of the Zr alloy. Furthermore, the values and trend of changes in their polycrystalline elastic properties when substituting Zr with Mo were correctly predicted by simulations. For the HESS, the simulated structural properties were successfully obtained. However, the theoretical elastic properties showed significant deviation from experimental results, indicating room for improvement in the sampling methodology and suggesting that accurately representing spins in the lattice may considerably affect the elastic properties of the alloy, necessitating further attention. A comparison of the average elastic modulus E and Poisson\'s ratio γ values obtained through simulations and experiments overall presented a good match with coherent results for all systems, when compared to the typical accuracy of density functional theory for pure transition metals. This work demonstrates that the maximum entropy model can effectively characterize high-entropy alloys under different approaches and emphasizes the importance of averaging different supercells and developing a sampling method for simulating chemically disordered materials. It also highlights the major contributions from integrating experimental and theoretical approaches to the study and characterization of novel high-entropy alloys.